Approaches Of Teaching Linguistic Competence - Khakimova, Malika (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article explores various pedagogical approaches employed in developing linguistic competence among students learning a foreign language. It reviews traditional, structural, communicative, task-based, and technology-integrated approaches, analyzing their theoretical underpinnings, implementation strategies, and effectiveness in fostering grammatical, lexical, and phonological knowledge. The paper also discusses the importance of adapting instructional methods to learner needs and contextual factors.